Developing a Co‐Designed Strategy to Improve Labor Monitoring and Management in India Using the World Health Organization Labour Care Guide: A Mixed‐Methods Formative Study. - Armari, Elizabeth; Vernekar, Sunil S.; Pujar, Yeshita; Pingray, Veronica; Althabe, Fernando; Gibbons, Luz; Berrueta, Mabel; Ciganda, Alvaro; Rodriguez, Rocio; Kumar, Jayashree Ashok; Patil, Shruti Bhavi; Karinagannanavar, Aravind; et al. (Birth: Issues in Perinatal Care, 2026)
Introduction: Nearly half of all perinatal deaths occur during the intrapartum period due to inadequate labor monitoring and intervention. The partograph, a paper‐based labor monitoring tool, can assist providers in recognizing and acting on early signs of fetal–maternal distress if used effectively. In 2020, the World Health Organization (WHO) developed a "next generation" partograph called the Labour Care Guide. There is limited evidence of how to optimize the use and impact of this new tool. This study describes the development of a co‐designed LCG implementation strategy in Karnataka, India. Methods: A targeted literature review, primary research across four public maternity hospitals (provider survey and facility assessment), and a 2‐day co‐design workshop with stakeholders were conducted. Findings were mapped to six target behaviors using the Theoretical Domains Framework (TDF) and the Capability, Opportunity, and Motivation‐Behavior (COM‐B) model to identify potential barriers and facilitators to LCG use. Consultations with local stakeholders explored these factors, and a 1‐week pilot informed final refinements of the strategy. Results: The LCG implementation strategy comprised an evidence‐based provider training program centered on "low dose, high frequency" principles, and monthly audit and feedback cycles, which in turn, relies on an enabling practice environment (supportive national policy frameworks, facility‐level guidelines, external partnerships, senior support, defining provider roles and expectations and adequate equipment and resources) to support its implementation. Conclusion: Effective use of the LCG needs a robust, context‐sensitive implementation strategy. We present the first evidence‐based, co‐designed LCG implementation strategy which can be used to support LCG dissemination and uptake.